Molecular characterization of methicillin resistant Staphylococcus aureus isolated from hospitals environments and patients in Northern Palestine (Epidemiology, Biostatistics, and Public Health, 2022)
BACKGROUND: Staphylococcus aureus (S. aureus) is considered one of the most common pathogen to humans. Infections caused by this mocroorganism can be acquired through both hospital and community settings. This study was carried out to investigate molecular characterization of MRSA strains isolated from the patients and their environment in two hospitals (Rafidia hospital and Thabet hospital) inNorthern Palestine, and to determine the clonal identity between these strains and their possible contribution to nosocomial infections.METHODS: Two hundred sixty five swabbed samples were collected from these hospitals, S. aureus was isolated,  antibiotic resistant genes were Panton–Valentin leukocidin (PVL) gene were detected and SCCmec and spA were typed by PCR and/or sequencing.RESULTS: The prevalence of MRSA among S. aureus isolates was 29% and 8.2% in Rafidia hospital and Thabet hospital, respectively. All strains resistant to oxacilllin disk were carried mecA gene. Majority of strains (84.6%) carried SCCmec type II (n = 11), type IVa and non-typeable were also detected. In addition, PVL was detected in 2 (14.3%) clinical strains. ERIC PCR patterns revealed that 2 strains recovered from patient bed and nasal swab isolated from Thabet Hospital were nontypeable, spA typing showed that they belonged to type t386 and have identical DNA sequences. Other 2 clinical isolates were spa typed, one belonged to clone t044, while the other is new clone not exist in database.CONCLUSIONS: Results may give evidence that environmental contamination possibly contributing to nosocomial infections.